2022
DOI: 10.1186/s12902-022-01157-6
|View full text |Cite
|
Sign up to set email alerts
|

The triglyceride glucose index is associated with future cardiovascular disease nonlinearly in middle-aged and elderly Chinese adults

Abstract: Objective We aimed to investigate the association between triglyceride glucose index and cardiovascular disease (CVD) development in the Chinese middle-aged and elderly population using the China Health and Retirement Longitudinal Study dataset 2011–2018. Methods Basic characteristics of participants, including sociodemographic information, and health conditions, were acquired. Logistic regression analyses and restricted cubic spline regression ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
2
8
1
Order By: Relevance
“…Finally, IR may be a process that causes diabetes and hypertension (24), A high level of TyG index can act as a surrogate biomarker of IR and cause lipotoxicity in the cardiovascular system in addition to the harmful vascular remodeling caused by oxygenation and systemic in ammation. Together, these elements-along with dyslipidemia and hypertension-increase the risk of CVD (25). This provides strong support for the hypothesis that a high TyG index can be a reliable biomarker for the development of cardiovascular disease.…”
Section: Discussionsupporting
confidence: 54%
“…Finally, IR may be a process that causes diabetes and hypertension (24), A high level of TyG index can act as a surrogate biomarker of IR and cause lipotoxicity in the cardiovascular system in addition to the harmful vascular remodeling caused by oxygenation and systemic in ammation. Together, these elements-along with dyslipidemia and hypertension-increase the risk of CVD (25). This provides strong support for the hypothesis that a high TyG index can be a reliable biomarker for the development of cardiovascular disease.…”
Section: Discussionsupporting
confidence: 54%
“…Studies have shown that TyG-index plays a significant role in CHD incidence in women [31,32,34,35,43,47,48], while one study reported a greater role in men [6],and another found no gender differences [44]. In this study, the association was found in both genders but only subsisted in women after multivariable adjustment.…”
Section: Tyg-index and Gendercontrasting
confidence: 49%
“…Regardless of improved prevention methods and treatment techniques [1,2], it is still the leading cause of morbidity and mortality worldwide, representing 32% of all deaths [3,4] and mortality worldwide, representing 32% of all deaths and an enormous weight to the national health finances [5,6].Thus, CHD risk assessment is a global public health priority.…”
Section: Introductionmentioning
confidence: 99%
“…Second. As mentioned earlier, IR can disrupt glucose metabolism, leading to compensatory increases in β-cell insulin production and hyperinsulinemia, which in turn leads to diabetes and other metabolic diseases closely related to CVD and CAC [ 40 , 41 ]. For example, Won et al confirmed that IR, represented by the TyG index, is an independent predictor of CAC progression, especially in adults with less severe baseline CAC [ 42 ].…”
Section: Discussionmentioning
confidence: 99%